2022
DOI: 10.1177/17579139211055497
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to delivering bystander cardiopulmonary resuscitation in deprived communities: a systematic review

Abstract: Background: There is a higher incidence of cardiac arrest in economically deprived areas; however, data show that bystander cardiopulmonary resuscitation (CPR) in those areas is lower. This results in lower survival rates, placing those communities at a double disadvantage. This systematic review explored the barriers and facilitators to engaging with bystander CPR in deprived communities. Methods: Studies were eligible for inclusion if they addressed any barrier or facilitator to performing bystander CPR or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
4
18
0
1
Order By: Relevance
“…6 Alongside the RSV associations, the study revealed the positive correlation of bystander CPR rate with country's population growth, birth rate, and the percentage of individuals using the Internet and the negative correlation of bystander CPR with population death rate, mortality from road traffic injuries, poverty, and unemployment rates. This is in line with previous research showing that socioeconomically-advantaged communities have higher engagement of bystanders in response to OHCA 12,13 that for instance could be related with better availability of public CPR education 14 or implementation of other system-level interventions known to be effective in improving bystander CPR rates (eg, dispatch-assisted CPR programs).…”
Section: Discussionsupporting
confidence: 92%
“…6 Alongside the RSV associations, the study revealed the positive correlation of bystander CPR rate with country's population growth, birth rate, and the percentage of individuals using the Internet and the negative correlation of bystander CPR with population death rate, mortality from road traffic injuries, poverty, and unemployment rates. This is in line with previous research showing that socioeconomically-advantaged communities have higher engagement of bystanders in response to OHCA 12,13 that for instance could be related with better availability of public CPR education 14 or implementation of other system-level interventions known to be effective in improving bystander CPR rates (eg, dispatch-assisted CPR programs).…”
Section: Discussionsupporting
confidence: 92%
“…[13][14][15] This gives rise to questions regarding the reliability of participants subjective responses as to how they may act, versus how they do act when faced with a real OHCA event. However, the findings support more recent evidence; a review of BCPR in deprived communities identified that willingness to perform or learn BCPR was not influenced by deprivation, 29 rather a range of contextual and environ-mental factors determined administration of BCPR. 30 Factors other than individual SES are likely to contribute to lower levels of BCPR in deprived communities, such as cultural identity and social cohesion.…”
Section: Discussionsupporting
confidence: 77%
“…These findings were unexpected given the previously identified association between BCPR rates and social deprivation in the region 5,17 , and evidence that individuals experiencing OHCA are less likely to receive BCPR in deprived areas. [14][15][16] However, the findings support more recent evidence; a review of BCPR in deprived communities identified that willingness to perform or learn BCPR was not influenced by deprivation 28 , rather a range of contextual and environmental factors determined administration of BCPR. 29 Factors other than individual SES are likely to contribute to lower levels of BCPR in deprived communities, such as cultural identity and social cohesion.…”
Section: Discussionsupporting
confidence: 71%
“…Categories of employment status derived from the UK Household Longitudinal Study 25 ; categories of household income from the Government Statistical Service 26 and occupation classifications from the Office of National Statistics. 28 Patient/public involvement helped develop relevant questions and piloted the survey instrument to ensure face validity, appropriateness and brevity. Feedback was incorporated into the final version of the survey instrument.…”
Section: Design and Development Of The Survey Instrumentmentioning
confidence: 99%